2008
DOI: 10.4161/cbt.7.12.7460
|View full text |Cite
|
Sign up to set email alerts
|

TNFSF10 (TRAIL), a p53 target gene that mediates p53-dependent cell death

Abstract: We have identified TNFSF10 (TRAIL) as a p53-transcriptional target gene. There are two p53 DNA-binding sites in the human TNFSF10 promoter region, at 346 and 625 bp upstream of the transcription start site. A human p53-expressing adenovirus (Ad-p53) induced TRAIL mRNA and protein expression in HCT116 p53-/- human colon cancer cells. A human TRAIL-promoter reporter assay showed increased luciferase activity with the promoter vector that contains two p53 DNA-binding motifs,following Ad-p53 infection, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 7 publications
3
85
0
Order By: Relevance
“…We however detected upregulated death receptors, Fas and TRAIL receptor molecules, as reported previously. 16 These biochemical data suggested that Ad-p53 activated primarily the extrinsic pathway in contrast to CDDP treatments that activated the both pathways. Shinoura et al 17 demonstrated enhanced apoptosis by a combination of Ad-p53 and forced expressions of Apaf-1 and caspase-9, suggesting less involvement of the intrinsic pathways by Ad-p53.…”
Section: Discussionmentioning
confidence: 91%
“…We however detected upregulated death receptors, Fas and TRAIL receptor molecules, as reported previously. 16 These biochemical data suggested that Ad-p53 activated primarily the extrinsic pathway in contrast to CDDP treatments that activated the both pathways. Shinoura et al 17 demonstrated enhanced apoptosis by a combination of Ad-p53 and forced expressions of Apaf-1 and caspase-9, suggesting less involvement of the intrinsic pathways by Ad-p53.…”
Section: Discussionmentioning
confidence: 91%
“…35,36 Recently, some researches developed targeted or inducible vector systems. [37][38][39][40][41][42] Herein, we used the E1 deleted vector and tumor cell specific promoter, hTERT, to drive the hTRAIL gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…1, 4-6). Despite its regulation by p53 (7), the apoptogenic action of TRAIL or other member of the TNF family (8) is largely independent of p53 integrity (9).…”
Section: Introductionmentioning
confidence: 99%